Análise da percepção da poluição sonora na feira de Bragança (Pará) - FARIAS, Pâmela Vitória de Sousa (2024)
Since noise pollution is considered the second largest form of pollution, this work analyzed the perception of stallholders at the Free Market in the city of Bragança (Pará) in relation to this environmental problem. The questionnaire applied investigated the perception that the interviewees had on this subject, how noise pollution affected their health, what types of noise bothered them the most, and in which areas the noise was greatest. The data collected showed that the majority (83%) of those interviewed remained aware of noise pollution. Likewise, 92% of those interviewed were aware of noise pollution and 94% felt uncomfortable with the noise at the fair. Lack of concentration, headache and irritability, lack of sleep, earache, etc. were the reactions caused by noise most reported by interviewees. When questioned, the interviewees were willing to undergo an audiometry exam, thus enabling their hearing health to be assessed, however they wanted this exam to be carried out right there at the Bragança Free Market. According to the evaluation of the data collected in the research, it was certified that the interviewees are clear and sensitive when it comes to noise pollution and warn that it is causing problems to their health.